2018
DOI: 10.3329/bjas.v47i1.39396
|View full text |Cite
|
Sign up to set email alerts
|

Goat production system at Mymensingh district in Bangladesh

Abstract: The experiment was conducted to investigate the present status and potentialities of organic goat production in Mymensingh district of Bangladesh through field survey. The data were collected through an interview schedule personally from 45 respondents in 3 villages of Bhaluka upazila who were involved in goat production. Parameters studied were check list for organic goat production likes origin, feeds and fodder, breeding, health care, living conditions and record keeping of livestock and factors related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…Besides, organic farming may be an essential part of the future of the food systems, together with a dramatic change in the food culture and reduction of antimicrobials in food [92]. Some studies have demonstrated that organic farms harbor fewer antimicrobial-resistant organisms compared to conventional methods [93][94][95] and also reduce the usages of antibiotics [96]. In organic livestock production systems, the producers need to follow a set of standards.…”
Section: Development Of Organic Productionmentioning
confidence: 99%
“…Besides, organic farming may be an essential part of the future of the food systems, together with a dramatic change in the food culture and reduction of antimicrobials in food [92]. Some studies have demonstrated that organic farms harbor fewer antimicrobial-resistant organisms compared to conventional methods [93][94][95] and also reduce the usages of antibiotics [96]. In organic livestock production systems, the producers need to follow a set of standards.…”
Section: Development Of Organic Productionmentioning
confidence: 99%
“…The results support those of Islam et al (2018) andTanwar et al (2010) who discovered that the majority of goat farmers lacked a high school diploma. According to Kumar et al (2018) and the majority of goalkeepers have a primary occupation in agriculture and raise goats as a side business. The majority of goat farmers, according to Islam et al (2018) were in the medium age bracket, followed by senior farmers and young farmers, which is somewhat similar to our findings.…”
Section: Socio-economic Status Of Farmersmentioning
confidence: 99%
“…Besides, organic farming may be an essential part of the future of the food systems, together with a dramatic change in the food culture and reduction of antibiotics in food (Muller et al, 2017). Some studies have demonstrated that organic farms harbor fewer antibiotic-resistant organisms compared to conventional methods (Sapkota et al, 2014(Sapkota et al, , 2011Schwaiger et al, 2010) and also reduce the usage of antibiotics (Kumar et al, 2018). Organic livestock production systems require producers to adhere to a number of standards.…”
Section: Development Of Organic Livestock Productionmentioning
confidence: 99%